Doze horas : o mito individual em uma autobioficção - Tenório, Patricia Gonçalves (2018)
Twelve hours is an essayist novel in three layers. Narrated in the third person singular, tells the story of Arabella Fantini, forty-five years old, single and childless, born in Recife, resident in Porto Alegre, Brazil, and museologist at the Art Museum of Rio Grande do Sul – MARGS. She brings up unknown artists and, one fine afternoon, receives the letter with photographs of the work of Fernandes Vieira, Portuguese artist that the sender claims to have met her father, who has disappeared since the museologist’s thirteenth birthday. All the narration is done during the twelve hours flight to Lisbon, rescuing the past, describing the present, anticipating the future, creating imaginary dialogues with “the man next door”. This is the first layer. The second layer is narrated in the first person singular, by a PhD student in Creative Writing, Manoela. It is understood that she studies in PUCRS, and would be a mimesis of the process of construction of the present thesis. The third layer is in the theoretical essay (in the impersonality of the first person plural), with the attached Logbook (in the vicinity of the first person singular). The theoretical essay has as objectives, in the light of the concepts of autobiography, autofiction and diary found in The autobiographical pact – by Rousseau to the internet, from the French essayist and sociologist Philippe Lejeune, and “The individual myth of the neurotic”, from the French psychoanalyst Jacques Lacan, to investigate the interchangeable layers of the thesis, as well as to present the hybrid genre of autobiofiction.